Innovation Technologies for Human Microbiome Improvement - Yankovsky, D.S.; Shirobokov, V.P.; Dyment, G.S. (Science and Innovation, 2024)
Introduction. In recent years, the human microbiome studies have been a relevant direction of biomedical sciences. A progress in the modern science has enabled to consider the microbiome as an additional human organ. It is involved in digestion and many other metabolic processes, as well as in maintaining the integrity of epithelial barrier, organizing the colonization resistance, neutralizing endo- and exogenous toxins, developing and maintaining the immune system and other physiologic functions; also, it optimizes conditions for normal functioning of the human organism as a whole. Therefore, maintaining the physiologic state of microbiome at all stages of the human life, from the early life till the extreme old age, has an enormous importance for promoting good health of population at any age. Problems. There has been observed an increase in the number of children and adults suffering from diseases associated with microbiome dysfunctions. Therefore, developing innovative means for microbiome improvement and creation of new methodologies for their clinical application is an important contribution to maintenance of the public health, treatment and prevention of many diseases. Purpose. Developing innovative technologies for human microbiome improvement. Materials and Methods. Methods for theoretical generalization, microbiological, biochemical and genetic research methods. Results. Modern research in the field of human microbial ecology has been generalized. New generation technologies for producing means of microbiome improvement have been developed. Treatment regimens have been created for patients with different profiles. Conclusion. Innovative biological technologies that provide means of microbiome improvement with high multifunctional biotherapeutic efficiency have been created. In particular, new generation multiprobiotics, unique enterosorbent prebiotics, and complex means of probiotic and sorption therapy have been designed. The results ensure effective means that facilitate the formation, maintenance, and restoration of healthy microbiome at all stages of human ontogenesis, from the birth to the extreme old age.